Chinese medicinal plants: an alternative approach for management of Verticillium wilt of cotton - KHASKHELI, Muhammad; SUN, Jun; HE, Shou; PAN, Zhao; JIA, Yin; ZHU, He; KHASKHELI, Allah; DU, Xiong (Phytopathologia Mediterranea, 2017)
Summary. The use of chemical fungicides is costly and potentially harmful to the environment. The trend towards the environmentally-friendly pesticides has led to the search for new antifungal agents from various sources, including Chinese medicinal herbs. This study aimed to confirm the antifungal potential of selected Chinese medicinal herbs, under in vitro and greenhouse conditions, against Verticillium dahliae, the causal agent of Verticillium wilt of cotton. Preliminary screening of 26 medicinal herbs for antifungal potential showed varied responses, reducing the radial colony growth of V. dahliae, and fungicidal potential. The strongest efficacy was observed for extracts from Prunus mume and Rhus chinensis, followed by Coptis chinensis, Cortex phellodendri chinensis (dried bark of Phellodendron chinense) and Curcuma longa. The efficacy of the four most effective herbs (R. chinensis, P. mume, C. chinensis and C. phellodendri chinensis) under greenhouse conditions correlated with in vitro tests. However, Prunus mume and Rhus chinensis gave the greatest reduction in severity of Verticillium wilt. The greatest improvements in plant height, fresh weight and number of leaves were obtained with P. mume and R. chinensis, followed by C. chinensis and C. phellodendri chinensis. Greatest improvements in plant growth resulted from P. mume and R. chi-nensis. Alternative control with Chinese medicinal herbs showing the greatest antifungal potential could provide economical, safe and non-hazardous tools for management of Verticillium wilt and increased cotton quality from sustainable production.